Word learning and verbal working memory in children with developmental language disorder. (March 2021) - Jackson, Emily; Leitão, Suze; Claessen, Mary; Boyes, Mark
Background and aims: Previous research into word learning in children with developmental language disorder (DLD) indicates that the learning of word forms and meanings, rather than form-referent links, is problematic. This difficulty appears to arise with impaired encoding, while retention of word knowledge remains intact. Evidence also suggests that word learning skills may be related to verbal working memory. We aimed to substantiate these findings in the current study by exploring word learning over a series of days. Methods: Fifty children with DLD (mean age 6; 11, 72% male) and 54 age-matched typically developing (TD) children (mean age 6; 10, 56% male) were taught eight novel words across a four-day word learning protocol. Day 1 measured encoding, Days 2 and 3 measured re-encoding, and Day 4 assessed retention. At each day, word learning success was evaluated using Naming, Recognition, Description, and Identification tasks. Results: Children with DLD showed comparable performance to the TD group on the Identification task, indicating an intact ability to learn the form-referent links. In contrast, children with DLD performed significantly worse for Naming and Recognition (signifying an impaired ability to learn novel word forms), and for Description, indicating problems establishing new word meanings. These deficits for the DLD group were apparent at Days 1, 2, and 3 of testing, indicating impairments with initial encoding and re-encoding; however, the DLD and TD groups demonstrated a similar rate of learning. All children found the retention assessments at Day 4 difficult, and there were no significant group differences. Finally, verbal working memory emerged as a significant moderator of performance on the Naming and Recognition tasks, such that children with DLD and poor verbal working memory had the lowest levels of accuracy. Conclusions: This study demonstrates that children with DLD struggle with learning novel word forms and meanings, but are unimpaired in their ability to establish new form-referent links. The findings suggest that the word learning deficit may be attributed to problems with encoding, rather than with retention, of new word knowledge; however, further exploration is required given the poor performance of both groups for retention testing. Furthermore, we found evidence that an impaired ability to learn word forms may only be apparent in children who have DLD and low levels of verbal working memory. Implications: When working with children with DLD, speech-language pathologists should assess word learning using tasks that evaluate the ability to learn word forms, meanings, and form-referent links to develop a profile of individual word learning strengths and weaknesses. Clinicians should also assess verbal working memory to identify children at particular risk of word learning deficits. Future research should explore the notion of optimal intervention intensity for facilitating word learning in children with poor language and verbal working memory.